1987
DOI: 10.1139/z87-442
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of pearl dace (Pisces, Cyprinidae) to alarm substance: time-course of behavior, brain amines, and stress physiology

Abstract: Pearl dace, Semotilus margarita (Pisces, Cyprinidae), respond behaviorally and physiologically to conspecific alarm substance. The behavioral alarm reaction was biphasic. A brief initial phase of rapid and unpredictable swimming was followed by a period of inactivity that was observable even after 5 h. In nature, biphasic behavioral reactions may function to remove alarmed fish from the area of greatest danger and then render them inconspicuous. The physiological alarm reaction included elements of a stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…Ide et al (2003) also did not find any effect of conspecifics alarm substance on plasma cortisol and glucose in Brycon cephalus after 30 minutes of exposure. However, 15 min of exposure to the alarm substance raised plasma cortisol levels in Semotilus margarita (Rehnberg et al, 1987). This is the first report analyzing a possible cortisol response in R. quelen submitted to skin extracts.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Ide et al (2003) also did not find any effect of conspecifics alarm substance on plasma cortisol and glucose in Brycon cephalus after 30 minutes of exposure. However, 15 min of exposure to the alarm substance raised plasma cortisol levels in Semotilus margarita (Rehnberg et al, 1987). This is the first report analyzing a possible cortisol response in R. quelen submitted to skin extracts.…”
Section: Discussionmentioning
confidence: 66%
“…Alarm cells are typically described in fish of the superorder Ostariophysi, where the number of species studied is variable among its five orders. Reviewing the literature we found no studies on the Gonorynchiformes order; in Cypriniformes, studies focus primarily on four species: Danio rerio (e.g., Suboski et al, 1990, Parra et al, 2009Wisenden et al, 2010); Margariscus margarita (e.g., Rehnberg et al, 1987); Pimephales promelas (e.g., Lawrence & Smith, 1989;Chivers & Smith, 1994;Wisenden & Smith, 1997;Wisenden & Smith, 1998;Wisenden & Thiel, 2002;Wisenden & Barbour, 2005;Chivers et al, 2007;CarreauGreen et al, 2008;Jung & Tonn, 2011), and Pseudorasbora parva (e.g., Sunardi-Takashi & Manatunge, 2007). In Gymnotiformes, there are reports of the presence of alarm cells, but without direct evidence of alarm substances (e.g., Smith, 1992;Wisenden & Barbour, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Plasma cortisol levels were significantly elevated compared with those of controls at 15·min and 30·min after stimulus introduction but returned to basal concentrations after 60·min. Rehnberg et al (1987) observed a significant elevation of plasma cortisol levels 15·min after introduction of alarm substance to pearl dace (Semotilus margarita), and this response was also insignificant compared with controls 1·h after alarm substance introduction. Cortisol is an important hormone in the integrated stress response, functioning as both a glucocorticoid and mineralocorticoid (Wendelaar Bonga, 1997).…”
Section: Discussionmentioning
confidence: 89%
“…Many different aspects of the integrated stress response have been observed in fish after detection of alarm substance, including elevated plasma cortisol and glucose (Rehnberg et al, 1987), increased respiration rate (Lebedeva et al, 1993) and sharpened optical alertness (indicated by dorsal light responsiveness; Pfeiffer and Riegelbauer, 1978).…”
mentioning
confidence: 99%